2013
DOI: 10.1007/s00408-013-9542-9
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Exercise and Respiratory Training Improves Respiratory Muscle Function in Pulmonary Hypertension

Abstract: Exercise and respiratory training as an adjunct to medical therapy may be effective in patients with PAH to improve respiratory muscle strength and exercise capacity. Future, randomized, controlled trials should be carried out to further investigate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 34 publications
2
70
0
11
Order By: Relevance
“…On median follow-up of 29.5 months (range, 21-36 months), the proportion of participants alive was 91% (12 deaths), and the proportion of participants with transplant-free survival was 89%. 18 Grünig et al 2012 19 Grünig et al 2012 20 Nagel et al 2012 27 Becker-Grünig et al 2013 21 Kabitz et al 2014 24 • 3 wk supervised training followed by 12 wk training at home • 1.5-h exercise training per day (in intervals distributed over the day) consisting of interval bicycle ergometer training at low workloads (10-60 W) 7 days a week • Dumbbell training of single muscle groups using low weights (500-1000g) …”
Section: Safety Of Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…On median follow-up of 29.5 months (range, 21-36 months), the proportion of participants alive was 91% (12 deaths), and the proportion of participants with transplant-free survival was 89%. 18 Grünig et al 2012 19 Grünig et al 2012 20 Nagel et al 2012 27 Becker-Grünig et al 2013 21 Kabitz et al 2014 24 • 3 wk supervised training followed by 12 wk training at home • 1.5-h exercise training per day (in intervals distributed over the day) consisting of interval bicycle ergometer training at low workloads (10-60 W) 7 days a week • Dumbbell training of single muscle groups using low weights (500-1000g) …”
Section: Safety Of Exercise Trainingmentioning
confidence: 99%
“…Several small studies have evaluated exercise training as an adjunctive therapeutic strategy in patients with chronic pulmonary hypertension. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although most of these studies were small and not designed to address clinical end points, such as mortality or hospitalizations, related to pulmonary hypertension, they have demonstrated a variable degree of improvement in exercise tolerance and quality of life in response to training.Therefore, because of the uncertainty about the benefit of structured exercise training programs in patients with pulmonary hypertension, we performed this systematic review and meta-analysis to assess the efficacy and safety of structured exercise training regimens in patients with pulmonary hypertension. …”
mentioning
confidence: 99%
“…Respiratory muscle function has been shown to contribute to dyspnea, exercise limitation, [23][24][25][26] Furthermore, trials in interstitial lung disease and pulmonary hypertension showed improved exercise capacity, symptoms and quality of life following pulmonary rehabilitation with or without respiratory muscle training. [27][28][29] Marcisz et al 30 showed that FVC, forced expiratory volume in one second, VC, MVV, maximum midexpiratory flow rate 25-75%, and peak expiratory flow rate values were significantly decreased in SSc patients compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Large improvements in 6-min walk test (6MWT) distance were reported in several studies after only 3 weeks of ExT [67][68][69][70][71]. However, most of these programmes included walking training, which may directly act upon 6MWT distance.…”
Section: Improving Endurance Capacity Exercise Trainingmentioning
confidence: 99%